Pengaruh Metode Pembelajaran Problem Solving Terhadap Prestasi Belajar Matematika Siswa SD - Anwar Anwar; Sutisna Sutisna (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2022)
The purpose of this study is to find out the influence of problem solving learning methods on students' math learning achievement on fractional material in class V of SD Negri Palea. This research is a quantitative quasi experimental study, by applying Nonequivalent Control Group Design The population in this study was all students of class V SD Negeri Palea in the 2021/2022 school year which amounted to 30 students consisting of 2 classes that were simultaneously used as samples using saturated sampling techniques. The research instruments used are tests and questionnaires. The results of this study obtained that based on the results of descriptive analysis the average value of pretest of the results of mathematics study of experimental class students amounted to 34.66; The average postest grade of experimental grade students' math learning results was 62.33. The average pretest grade of students' math learning outcomes in the control class was 29.00; The average postest grade of student learning outcomes in the control class was 45.33. In addition, the average score of the questionnaire in the experimental class was 53.53; The average score in the control class was 48.66. Based on the results of inferential statistical tests using the t-test obtained a significant value of 0.000 < 0.05, which means H0 was rejected and H1 was accepted. So it can be concluded that there is an influence of problem solving learning methods on the achievement of learning mathematics students on fractional material in class V of SD Negeri Palea.